THE IMPACT OF SOCIAL MEDIA ON STUDENT LEARNING CASE STUDY: SMA YAPITA SURABAYA - Isnaini, Ulvi Rahma (Jurnal Sistem Komputer, 2016)
Nowadays student and teacher in Indonesia have a massive use of smart phones, tablet and other portable device. All these smart phones and other portable devices are equipped or ready for social media applications like Facebook, Twitter, YouTube, WhatsApp, and Instagram which are part of what is known as Social Media. Social media is a popular method for communication amongst students in Indonesia. However excessive social media use can raise questions about whether academic performance is affected. This paper aims to investigate the use of social media in teaching and learning as a scaffolding tool, and the impact of that on teachers and students with case study SMA Yapita Surabaya. The study implemented a 30-item questionnaire aimed to investigate student’s views in smart devices use and access, the current use of social website, the use of the web, views of the impact of social media on education, and views of possible impact of official use of social media on learning. It’s apparently that smart phone is the best possible device to enhance the use of social media in education, where more than three quarters of students have smart phones. For the internet access, 79% of students have internet access on their smartphone, and only 32% of them who have internet access at home. In regards the social media application, it is clear that Facebook as a main tool, with 89% of the student use this application. At the end, this research concludes that the teacher and the students need a series of training session to evaluate their own use of social media, and to enhance their abilities to use available properties.